2005
DOI: 10.1210/en.2005-0282
|View full text |Cite
|
Sign up to set email alerts
|

Src Homology 3-Domain Growth Factor Receptor-Bound 2-Like (Endophilin) Interacting Protein 1, a Novel Neuronal Protein that Regulates Energy Balance

Abstract: To identify genes involved in the central regulation of energy balance, we compared hypothalamic mRNA from lean and obese Psammomys obesus, a polygenic model of obesity, using differential display PCR. One mRNA transcript was observed to be elevated in obese, and obese diabetic, P. obesus compared with lean animals and was subsequently found to be increased 4-fold in the hypothalamus of lethal yellow agouti (A(y)/a) mice, a murine model of obesity and diabetes. Intracerebroventricular infusion of antisense oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
2
54
0
1
Order By: Relevance
“…Further studies demonstrated that SGIP1 has a role in regulating food intake, where targeted reduction of hypothalamic SGIP1 mRNA inhibited food intake and decreased body weight in both P. obesus and Sprague-Dawley rats. 16 As markers of the metabolic syndrome, we measured several diabetes/obesity-related phenotypes, including fasting plasma glucose, waist:hip ratio, BMI and fat mass. We genotyped 47 polymorphic SNPs in SGIP1 selected for the potential to confer a functional effect on the gene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies demonstrated that SGIP1 has a role in regulating food intake, where targeted reduction of hypothalamic SGIP1 mRNA inhibited food intake and decreased body weight in both P. obesus and Sprague-Dawley rats. 16 As markers of the metabolic syndrome, we measured several diabetes/obesity-related phenotypes, including fasting plasma glucose, waist:hip ratio, BMI and fat mass. We genotyped 47 polymorphic SNPs in SGIP1 selected for the potential to confer a functional effect on the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depletion of hypothalamic SGIP1 mRNA reduced body weight by inducing an inappropriately high metabolic rate. 16 Whether genetic variation in the SGIP1 gene acts to alter SGIP1 protein expression remains to be seen and is an important question for future experiments.…”
Section: Sh3-domain Grb2-like (Endophilin)-interacting Protein 1 N Cumentioning
confidence: 99%
See 3 more Smart Citations